CACNA1A-associated epilepsy: Electroclinical findings and treatment response on seizures in 18 patients. (July 2021) - Le Roux, Marie; Barth, Magalie; Gueden, Sophie; Desbordes de Cepoy, Patrick; Aeby, Alec; Vilain, Catheline; Hirsch, Edouard; de Saint Martin, Anne; Portes, Vincent des; Lesca, Gaëtan; Riquet, Audrey; Chaton, Laurence; et al.
Abstract: CACNA1A pathogenic mutations are involved in various neurological phenotypes including episodic ataxia (EA2), spinocerebellar ataxia (SCA6), and familial hemiplegic migraine (FHM1). Epilepsy is poorly documented. We studied 18 patients (10 males) carrying de novo or inherited CACNA1A mutations, with median age of 2, 5 years at epilepsy onset. Eight mutations were novel. Two variants known leading to gain of function (GOF) were found in 5 patients. Five other patients had non-sense variants leading to loss of function (LOF). Seizures were most often revealed by either status epilepticus (SE) (n = 8), eventually triggered by fever (n = 5), or absences/behavioural arrests (n = 7). Non-epileptic paroxysmal events were frequent and consisted in recurrent hemiplegic accesses (n = 9), jitteriness in the neonatal period (n = 6), and ocular paroxysmal events (n = 9). Most of the patients had early permanent cerebellar dysfunction (n = 16) and early moderate to severe global developmental delay (GDD)/intellectual deficiency (ID) (n = 17). MRI was often abnormal, with cerebellar (n = 8) and/or cerebral (n = 6) atrophy. Stroke-like occurred in 2 cases. Some antiepileptic drugs including topiramate, levetiracetam, lamotrigine and valproate were effective on seizures. Acetazolamide and calcium channel blockers were often effective when used. More than half of the patients had refractory epilepsy. CACNA1A mutation should be evoked in front of 2 main electro-clinical phenotypes that are associated with permanent cerebellar dysfunction and moderate to severe GDD/ID. The first one, found in all 5 patients with GOF variants, is characterized by intractable seizures, early and recurrent SE and hemiplegic accesses. The second, less severe, found in 5 patients with LOF variants, is characterized by refractory early onset absence seizures. Highlights: CACNA1A variants result in 2 different electro-clinical phenotypes: intractable seizures associated with early and recurrent status epilepticus and hemiplegic accesses, and early onset refractory absence seizures. Functional studies suggest that the first electro-clinical phenotype is associated with a gain of function, and that the second one is associated with a loss of function. Epilepsy related with CACNA1A variants is associated with cerebellar dysfunction and early neurodevelopmental impairment. Drug resistance is very frequent in epileptic CACNA1A patients.